2007
DOI: 10.1177/0272989x06297101
|View full text |Cite
|
Sign up to set email alerts
|

Further Insight into the Perception of Quantitative Information: Judgments of Gist in Treatment Decisions

Abstract: For supporting older people's judgments of relative extent, risk information is best presented using vertical bars with a scale; the format systematic ovals with a scale are among the next most easily processed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
104
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 41 publications
7
104
3
Order By: Relevance
“…• Fourth, for judging which of two categories is bigger, tables, pie charts and bar charts tend to yield similar accuracy scores (Spence, et al 1991, Meyer, Shinar andLeiser 1997) though another study found that pie charts performed worse than bar charts (Feldman-Stewart, et al 2000). Providing a scale for this task improves accuracy, and providing the numerical value in addition reduced the time needed to complete the task (Feldman- Stewart, Brundage and Zotov 2007). When restricting time, tables perform worse (Spence, et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Fourth, for judging which of two categories is bigger, tables, pie charts and bar charts tend to yield similar accuracy scores (Spence, et al 1991, Meyer, Shinar andLeiser 1997) though another study found that pie charts performed worse than bar charts (Feldman-Stewart, et al 2000). Providing a scale for this task improves accuracy, and providing the numerical value in addition reduced the time needed to complete the task (Feldman- Stewart, Brundage and Zotov 2007). When restricting time, tables perform worse (Spence, et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that pictographs work well to communicate risks, especially for populations with lower numeracy (Fagerlin, Wang and Ubel 2005, Hawley, et al 2008, Garcia-Retamero and Galesic 2009. Another study comparing icon arrays filled with ovals, single bars (vertical or horizontal), and pie charts (with a single slice) found that a vertical bar chart yielded the greatest comprehension (Feldman -Stewart, et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…9,16 These graphics performed better than other formats (such as pie charts and random oval pictographs) with respect to ease (speed) of processing and accuracy. 9,16 However, pictographs were better overall on both tasks.…”
mentioning
confidence: 99%
“…9,16 These graphics performed better than other formats (such as pie charts and random oval pictographs) with respect to ease (speed) of processing and accuracy. 9,16 However, pictographs were better overall on both tasks. 9 In a second study, 16 numbers, percentages, and referent scales were added to the same graphics to examine their effects on the gist task only.…”
mentioning
confidence: 99%
“…Bar graphs are one of the most widely used graphical representations in the popular press [Schield 2006]. This format is often understood and preferred by patients for communication of health risks [Fortin et al 2001;Feldman-Stewart et al 2007]. This format was inspired by the use of bar graphs we observed in PatientsLikeMe and Lose It!…”
Section: Hip Design Formats Exploredmentioning
confidence: 99%